SOA modeling patterns for service-oriented discovery and analysis - Bell, Michael, 1957 June 22- (John Wiley & Sons, 2010)
"SOA Modeling Patterns for Service-Oriented Discovery and Analysis introduces a universal, easy-to-use, and nimble SOA language to facilitate the service identification and examination life cycle stage. This business and technological vocabulary will benefit your service development endeavors and foster organizational software asset reuse and consolidation, and reduction of expenditure. To help developers, business architects, technical architects, modelers, business analysts, team leaders, and managers to successfully discover and analyze services, an elaborate set of more than 100 patterns and anti-patterns are introduced. These are repeatable templates and SOA best practices that will guide practitioners to efficiently identify new services and analyze their feasibility for construction, deployment to production environments, and execution. This illustrated SOA book discusses in detail and depicts many service-oriented modeling examples for five major pattern groups: 1. Discovery and Analysis Road Map and Strategy Patterns 2. Service Discovery Process Patterns 3. Service Categorization Patterns 4. Service Contextual Analysis Process and Modeling Patterns 5. Service Structural Analysis Process and Modeling Patterns. Offering easy-to-understand SOA modeling language, notation, and discovery and analysis patterns, the book provides answers to the most common questions concerning service-oriented discovery and analysis life-cycle initiatives that face SOA practitioners. The book skillfully explores: How to discover services. How to analyze services for construction and production. How to assess service feasibility for deployment. How to employ the SOA modeling language during the service identification and examination process. How to utilize the SOA modeling patterns and anti-patterns for service discovery and analysis. Focusing on the Service-Oriented Discovery and Analysis Life Cycle Stage, the SOA modeling patterns that are introduced will help you to integrate business processes, concepts, legacy applications, and services into a valuable analysis proposition. This solution can be implemented by all technologies, software platforms, and languages. Furthermore, with the in-depth information garnered from SOA Modeling Patterns for Service-Oriented Discovery and Analysis, you will acquire a broad SOA Modeling knowledge base and reference that can increase efficiency and productivity in the workplace"--Provided by publisher.